2009
DOI: 10.1038/nm.1927
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells are key cerebroprotective immunomodulators in acute experimental stroke

Abstract: Systemic and local inflammatory processes have a key, mainly detrimental role in the pathophysiology of ischemic stroke. Currently, little is known about endogenous counterregulatory immune mechanisms. We examined the role of the key immunomodulators CD4(+)CD25(+) forkhead box P3 (Foxp3)(+) regulatory T lymphocytes (T(reg) cells), after experimental brain ischemia. Depletion of T(reg) cells profoundly increased delayed brain damage and deteriorated functional outcome. Absence of T(reg) cells augmented postisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
858
7
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 954 publications
(944 citation statements)
references
References 49 publications
50
858
7
5
Order By: Relevance
“…It was also found that CA1 pyramidal cell death, 1 day after OGD, was significantly increased in microglia-depleted organotypic cultures, again suggesting a neuroprotective role of the normal content of microglia (Montero et al 2009). Since it is well known that the CA3 area of the hippocampus is more resistant than the CA1 to ischemic insults, the increase of microglia cells that occurs in concert with the removal of dead cells (Nathan and Ding 2010) may have both anti-inflammatory effects and consequently neuroprotective properties (Liesz et al 2009). Indeed, the microglia increase in CA3 and decrease in CA1 (Lana et al 2014) may explain the higher sensitivity of CA1 pyramidal cells to an ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that CA1 pyramidal cell death, 1 day after OGD, was significantly increased in microglia-depleted organotypic cultures, again suggesting a neuroprotective role of the normal content of microglia (Montero et al 2009). Since it is well known that the CA3 area of the hippocampus is more resistant than the CA1 to ischemic insults, the increase of microglia cells that occurs in concert with the removal of dead cells (Nathan and Ding 2010) may have both anti-inflammatory effects and consequently neuroprotective properties (Liesz et al 2009). Indeed, the microglia increase in CA3 and decrease in CA1 (Lana et al 2014) may explain the higher sensitivity of CA1 pyramidal cells to an ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-10 is expressed as an anti-inflammatory cytokine that is produced from regulatory T lymphocytes (Treg). It was reported that IL-10 could suppress the neurotoxic functions of TNF-α and IFN-γ [21] and alleviate BBB damage. IL-10 is also conductive to the restoration of nerve cells and has a neuroprotective effect [22] .…”
Section: Discussionmentioning
confidence: 99%
“…A substantial role for the adaptive immune response after stroke is increasingly recognized. Transgenic animals deficient in lymphocytes consistently have smaller infarcts in different stroke models [23][24][25][26]. Moreover, antibody-mediated depletion of CD4 + , CD8 + , and γδ T cells reduced infarct volume and improved functional outcome [25,[27][28][29].…”
Section: Immune Mechanismsmentioning
confidence: 99%